Intelligent company: the ascription of human behaviour in real-time systems - Impett, Jonathan (New York Chapman and Hall/CRC, 2023)
Responses to AI vacillate between the epochal or post-human – Stephen Hawking foresees a tipping point when AI becomes able to set its own goals – and the thoroughly prosaic – the benefits of self-driving cars, flower-picking robots, or automated music transcription. For good reason, both aspects are very present in current discourse. In creative and cultural contexts, the very fact of an AI seems to dominate public and critical reception of a given work. Reviews of new AI-involving work of all kinds tend to focus on the perceived challenge to or automatization of humanness in general or authoriality in particular, rather than the ways in which human creativity might be extended. Critical and theoretical consideration of AI-involving work thus becomes unhelpfully separate from broader discussion of creative and cultural trends. In this chapter I will consider aspects of the potential role of AI in music performance in order to propose an alternative paradigm of AI as many-layered memory. Together, musician and AI seek instances of anamnesis which neither could accomplish alone. A practically oriented thought experiment explores possibilities for interface and navigation in such a performance system and creative practice. Hopefully the practical challenges will illuminate the broader issues.
FRIS
1
Keywords: Music, Thought and Technology